(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The aim of this work is the analysis of system of distribution in theoretical aspect and the verification of theory in practice for example the Analda – Żywiec Trade Ltd. – branch in Wejherowo. And the hypothesis of this work make the presumption, that the correctly constructed system of distribution assures the efficient delivering of the goods to the final customer.